Retention Ratio, Lock-Up Period and Prestige Signals and Their Relationship with Initial Public Offering (IPO) Return: Malaysian Evidence - Ali Albada; Othman Yong; Mohd. Ezani Mat Hassan; Ruzita Abdul-Rahim (Asian Academy of Management Journal of Accounting and Finance, 2018)
High-quality issuing firms with encouraging inside information regarding their prospect will use signalling to differentiate their issues from low-quality issuing firms and convince prospective investors regarding the value of their firm. Hence, the present study investigates the dominant signals in explaining the initial return in the Malaysian IPO market. The study investigates the following signalling variables: Lock-up period, shareholder retention ratio, underwriter reputation, auditor reputation and board reputation. Moreover, the current study also uses the stepwise regression analysis to know the order of contribution of the signalling variables to the overall model. The results of the regression analysis show that three signals out of five have a significant relationship with the initial return. Furthermore, the stepwise regression shows their order of contribution, where shareholder retention ratio is ranked first, followed by auditor reputation and board reputation. The outcomes of the present study offer new evidence regarding the kind of information that investors should be concerned with when evaluating IPOs and making decisions concerning investment in the Malaysian IPO market.